Answer:
x=-5, x=9
Step-by-step explanation:
we know that
The formula to solve a quadratic equation of the form
[tex]ax^{2} +bx+c=0[/tex]
is equal to
[tex]x=\frac{-b\pm\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]2x^{2} -8x-90[/tex]
equate to zero
[tex]2x^{2} -8x-90=0[/tex]
so
[tex]2=-1\\b=-8\\c=-90[/tex]
substitute in the formula
[tex]x=\frac{-(-8)\pm\sqrt{-8^{2}-4(2)(-90)}} {2(2)}[/tex]
[tex]x=\frac{8\pm\sqrt{784}} {4}[/tex]
[tex]x=\frac{8\pm28} {4}[/tex]
[tex]x=\frac{8+28} {4}=9[/tex]
[tex]x=\frac{8-28} {4}=-5[/tex]
therefore
The solutions are x=-5, x=9